Kewajiban Indonesia dalam Menangani Pengungsi Etnis Rohingya berdasarkan Hukum Internasional - Putu Ika Asri Madani (Jurnal Hukum Lex Generalis, 2025)
Ethnic Rohingya is a group that is systematically persecuted in Myanmar. The result of the persecution is the emergence of the Rohingya refugee crisis, including in Indonesia. This article aims to analyze the suitability of the Indonesian government's actions in handling the refugee crisis case. This article uses a normative legal research method, using the approach of legislation, cases and concepts. From the research conducted, it is found that Indonesia has attempted to comply with international law governing the handling of refugees, but a collaborative approach must be taken with UNHCR in order to ensure respect for human rights.